A 20-Year Single Center Experience of Right Lateral Sector Graft in Adult Living Donor Liver Transplantation With Special Reference to Biliary Complication - Tomoaki Hayakawa; Nobuhisa Akamatsu; Takashi Kokudo; Kyoji Ito; Yujiro Nishioka; Yujiro Mihara; Akihiko Ichida; Takeshi Takamoto; Yoshikuni Kawaguchi; Kiyoshi Hasegawa (Transplant International)
Right lateral sector grafts (RLSGs) in living donor liver transplantation (LDLT) expand donor options, however, their long-term outcomes and complication rates remain unclear. We analyzed 661 LDLTs (42 RLSGs, 363 right liver grafts, 243 left liver grafts, and 13 left lateral section grafts) performed between 2000 and 2021 at the University of Tokyo Hospital. RLSG donors experienced a 4.8% major complication (Clavien-Dindo grade ≥3b) rate with no mortality. RLSG recipients had a 38.1% major complication rate and a 9.5% 90-day mortality rate. Compared with other graft types, RLSG recipients had higher rates of hepatic artery thrombosis (9.5% vs. 3.1%), portal vein stenosis (14.3% vs. 1.9%), and biliary stricture (42.9% vs. 16.3%). The 5-year survival rate for RLSG recipients (79.2%) did not differ significantly from other graft types (84.7%). Graft bile ducts measuring >4 mm were associated with increased anastomotic biliary stricture. RLSG, the only option for 33 recipients, expanded the donor pool by 5%. Although RLSG is associated with higher vascular and biliary complication rates, it demonstrates favorable long-term survival and significantly expands the donor pool. For patients without suitable conventional graft options, RLSG represents a viable choice that provides life-saving transplantation opportunities.